EVALUATING CADRE SUPPORT IN MATERNAL FEEDING PRACTICES: INFLUENCE ON EATING PATTERN OF CHILDREN UNDER TWO - Ekayanti, Ikeu; Nurdiani, Reisi; Cantika, Aulia Dwi; Nadzifatussya’diyah; Nasution, Zuraidah (Universitas Airlangga, 2025)
Stunting remains a significant global health concern among children under two years old, underscoring the importance of maternal skills in food preparation to prevent this issue. This study evaluated the impact of Posyandu cadre training and support on maternal capacity and its relationship with Infant and Young Child Feeding (IYCF) practices. Seventy mothers and their children under the age of two, along with ten cadres, participated in this study. The intervention began with cadre training, followed by support for mothers. The results revealed that cadre knowledge of food material science (FMS) (p=0.033) and attitudes toward clean and healthy behavior (CHB) (p=0.038) significantly improved after training. Mothers demonstrated significant improvements in knowledge of FMS (p<0.001), Nutritional Requirements of Children Under Two (NRCT) (p<0.001), and CHB (p=0.041); attitudes toward complementary feeding (CF) (p=0.030). Cadre knowledge and maternal knowledge in FMS was found a significant correlation (p=0.026). However, cadre attitudes did not correlate with the knowledge and attitudes of the mother. The age of children under two was correlated with MMD (p=0.036), MMF (p=0.017), and MAD (p=0.036). Additionally, maternal attitudes toward food were associated with MMF (p=0.037) and dietary diversity (p=0.034) in children under the age of two. These findings underscore the significance of cadre training and maternal support programs in enhancing feeding practices, which may lead to improved nutritional outcomes. Strengthening the cadre's knowledge and skills could be key to promoting optimal IYCF practices.